PENGARUH KONSENTRASI AIR REBUSAN DAUN SIRSAK (Annona muricata Linn) TERHADAP PERTUMBUHAN LARVA NYAMUK Aedes aegypti - Ariana, Diah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PENGARUH KONSENTRASI AIR REBUSAN DAUN SIRSAK (Annona muricata Linn) TERHADAP PERTUMBUHAN LARVA NYAMUK Aedes aegyptiDiah Ariana, ST, M.Kes Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractLeaves of the soursop (Annona muricata Linn) Indonesia is known as a medicinal plant that can treat a variety of diseases other than as a cure soursop leaves is also an insecticide-producing plants are bioactive compounds known as acetogenin which are bioactive compounds in high concentrations can be toxic to insects, thus may cause the insects will not eat. At low concentrations of toxic by oral administration stomach and can cause death. Soursop leaves are pesticides from natural elements that can be decided by the Aedes aegypti mosquito generation above background can be taken formulation of the problem Is there any effect of the concentration of soursop leaves boiled water (Annona muricata Linn) on the growth of mosquito larvae of Aedes aegypti? This study aimed to determine the effect of water concentration on the growth of soursop leaf decoction Aedes aegypti mosquito larvae.The design of this study used an experimental design with laboratory testing, soursop leaf decoction obtained by weigh 100 g and dissolved in 100 ml of distilled water generated lau soursop leaves boiled water. The inhibition assay performed on boiled water boiling water concentration 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10% and visits by the number of larvae of Aedes aegypti mosquitoes that die in 24 hours after treatment. Statistical analysis using Annova test with significance level 0.05 for determining the presence or absence of the influence of water concentration on the growth of soursop leaf decoction mosquito Aedes aegypti and subsequent Tukey HSD test was done to see the differences in each concentration. The results showed concentrations of 10% to 100% can inhibit the growth of mosquito larvae of Aedes aegypti, so it can be concluded that the soursop leaves can inhibit the growth of mosquito larvae of Aedes aegypti and efficient soursop leaves is used for patients with antibacterial, antifungal, anticonvulsant, and anti-inflammatory.Keyword :Â  larvae of Aedes aegypti, soursop leaves